RETORIKA DAN PENGGUNAANNYA DALAM BERBAGAI BIDANG - Marta, I Nengah (Universitas Pendidikan Ganesha, 2010)
Rethoric is a field of knowledge, which studies speeking ability. Now, the use of it wides to manykinds of life, such as: politics, business, art, journalism, as well as education. The ability of usinglanguage rethorically will influence the audiences.Key words: rethoric, speeking ability, language